THE UPPER CRETACEOUS RADIOLARIANS, FORAMINIFERS, AND STRATIGRAPHY OF THE SOUTHEASTERN RUSSIAN PLATE, THE RIGHT-BANK VOLGA REGION NEAR VOLGOGRAD - Bragina L.G.; Ben'yamovskii V.N.; Zastrozhnov A.S. (My University, 1999)
Paleontological study of the Upper Cretaceous sediments from wells 502 and 28 in the Volgograd region revealed distinct radiolarian and foraminiferal assemblages. Two stratigraphic levels, Coniacian-Santonian and upper Campanian, are recognized on the basis of radiolarians. Foraminiferal and radiolarian zones of the same section are first correlated to each other in the Volgograd region, and coeval assemblages from the Moscow syneclise and Volgograd region are compared.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая